15=m+-9

Simple and best practice solution for 15=m+-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15=m+-9 equation:


Simplifying
15 = m + -9

Reorder the terms:
15 = -9 + m

Solving
15 = -9 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
15 + -1m = -9 + m + -1m

Combine like terms: m + -1m = 0
15 + -1m = -9 + 0
15 + -1m = -9

Add '-15' to each side of the equation.
15 + -15 + -1m = -9 + -15

Combine like terms: 15 + -15 = 0
0 + -1m = -9 + -15
-1m = -9 + -15

Combine like terms: -9 + -15 = -24
-1m = -24

Divide each side by '-1'.
m = 24

Simplifying
m = 24

See similar equations:

| 5n^2+8n-36=0 | | p^2-2px+x^2=y^2 | | 4(x+3)=14 | | t*6-5=15 | | 20/35*45/4= | | 3(4x+6y)=15 | | a*4+4=14 | | M^2+2m-1m-5m-10-1=0 | | x(x+12)=32 | | 7-0.03x=1.72+1.75 | | [4+2]=6 | | (n+8m)(n+3m)-(n+m)(n-4m)=7x | | 5x-2x+6=x+18 | | 3(4-3c)=c-6 | | 3p+5=2p+15 | | 8*x=72 | | -7(f+1)-6=-41f+55 | | x(x-3)(x+3)=0 | | .4y=9 | | 2z+3(x-5)=130 | | 8y-4=36 | | 2x^3-2x^2+6x-6=0 | | 7x-2=-21 | | c(N)=25+0.15 | | 5x^2-40+20=0 | | 9=2+6.7+.6Y | | 8timesx=72 | | 25+3h=49 | | 2,4(x-0,1)-0,26=2,4x-0,4 | | q(3q+4)=4 | | 15y+8=14 | | 6(3+x)=8(x-20) |

Equations solver categories